ECO-TEHNOLOGICAL ANALYSIS OF A MECHANICAL MANUFACTURING PROCESSING - Dan DOBROTA; Gheorghe AMZA (Fiabilitate şi Durabilitate)
Running machining processes determine the discharge in environment of different amounts of pollutants. In this way the analysis presented in this paper refers to all stages of the technological process starting with the pickling and cleaning of parts. So, it was found that pickling and cleaning processes parts cause environmental pollution with hydrochloric acid HCl and sulfuric acid H2SO4, and manufacturing processes cause the appearance of volatile compounds in atmosphere that may cause irritation of mucous membranes of working staff